A trial of telmisartan prevention of cardiovascular diseases (ATTEMPT-CVD): Biomarker study. (June 2016) - Ogawa, Hisao; Soejima, Hirofumi; Matsui, Kunihiko; Kim-Mitsuyama, Shokei; Yasuda, Osamu; Node, Koichi; Yamamuro, Megumi; Yamamoto, Eiichiro; Kataoka, Keiichiro; Jinnouchi, Hideaki; Sekigami, Taiji; ,
Aims: A trial of telmisartan prevention of cardiovascular disease (ATTEMPT-CVD) was performed to compare the effects of angiotensin II receptor blocker (ARB) therapy and those of non-ARB standard therapy on biomarker level changes and the incidence of cardiovascular events in hypertensive patients. Methods and results: In this multicenter, open-label, randomized, parallel-group, comparative study, the effects of ARB therapy and those of non-ARB standard therapy on urinary albumin creatinine ratio (UACR) and plasma brain natriuretic peptide (BNP) level changes were investigated for three years from the start of antihypertensive treatment as the primary endpoints. The incidences of cardiovascular composite events were compared between the two groups, and the relationship between the incidence of the events and biomarker changes were investigated as secondary endpoints. The study started with 615 patients in the ARB group and 613 patients in the non-ARB group. The ARB group had a significant effect on UACR and plasma BNP level changes compared with the non-ARB group. Fewer cardiovascular events occurred in the ARB group, but the difference was not statistically significant. UACR and plasma BNP levels at baseline were associated with cardiovascular events. Conclusion: This study provided the first evidence that ARB treatment caused a smaller increase in plasma BNP and a greater decrease in UACR than non-ARB treatment, independently of blood pressure control, and gives a novel insight into the significance of BNP and UACR as predictors of cardiovascular and renal risk on antihypertensive treatment.